2012
DOI: 10.1111/j.1365-313x.2012.04966.x
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐α‐xylosidase and trans‐β‐galactosidase activities, widespread in plants, modify and stabilize xyloglucan structures

Abstract: SUMMARYCell-wall components are hydrolysed by numerous plant glycosidase and glycanase activities. We investigated whether plant enzymes also modify xyloglucan structures by transglycosidase activities. Diverse angiosperm extracts exhibited transglycosidase activities that progressively transferred single sugar residues between xyloglucan heptasaccharide (XXXG or its reduced form, XXXGol) molecules, at 16 lM and above, creating octato decasaccharides plus smaller products. We measured remarkably high transglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Given that no boron‐metabolizing enzyme is yet known, we undertook a preliminary study of the possibility that a plant protein might catalyse the boron‐dependent dimerization of RG‐II, thus ‘mimicking’ the action of Pb 2+ . The potential source was an extract of parsley shoots, a proven rich source of numerous cell‐wall‐directed enzyme activities including xyloglucan endotransglucosylase (XET), glycosidases, glycanases, transglycosidases, transglycanases and pectin methylesterase ( GHATA base, ; Franková & Fry, , , ; D. Chormova & S. C. Fry, unpublished). When the parsley extract was incubated for 0–24 h with [ 3 H]RG‐II (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that no boron‐metabolizing enzyme is yet known, we undertook a preliminary study of the possibility that a plant protein might catalyse the boron‐dependent dimerization of RG‐II, thus ‘mimicking’ the action of Pb 2+ . The potential source was an extract of parsley shoots, a proven rich source of numerous cell‐wall‐directed enzyme activities including xyloglucan endotransglucosylase (XET), glycosidases, glycanases, transglycosidases, transglycanases and pectin methylesterase ( GHATA base, ; Franková & Fry, , , ; D. Chormova & S. C. Fry, unpublished). When the parsley extract was incubated for 0–24 h with [ 3 H]RG‐II (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Xyloglucan modifications in muro have been well studied in Arabidopsi s and mutants with changes in glycosidase activity, such as the Atxyl1, Atbgal10 and axy8 mutants [52-54] show significant alterations in the composition of the XEG-soluble polymers. It has recently been shown that trans-α-xylosidases and trans-β-galactosidases can act directly on the xyloglucan polysaccharide to cause modification [55]. …”
Section: Discussionmentioning
confidence: 99%
“…This catalytic sluggishness is likely to be correlated with more energy-demanding TS (for both glycosylation and deglycosylation steps), which lower overall catalytic turnover. mixed activity) [70][71][72][73][74][75]. Of course, this is a rather simplistic view of enzyme evolution and other data suggest that enzymes might have evolved in both directions [68,69], and indeed some GHs (mainly from plants) display both hydrolysis and transglycosylation activities and thus present intermediate cases (i.e.…”
Section: Naturally Occurring Transglycosylases: Elucidating Nature's mentioning
confidence: 99%